Mechanical properties of jute and palm fiber reinforced hybrid polypropylene composites - Aminudin, Bin Abdul Kadir. (Universiti Malaysia Sarawak (UNIMAS), 2009)
Composite material is types of material that have variation of strength. It can be used in many fields because of their wide range of strength. Research on composites continuously performed to overcome dependencies on traditional material such as metal. The concerns in biodegradable material has made composite become more popular car manufacturer and other industries. This project describes the mechanical properties of jute and oil palm fiber reinforced hybrid composites and the effect of their fiber content. In obtaining the mechanical properties, there are three types of test conducted. There are tensile test, flexural test and water absorption test. This test conducted according to ASTM D 638, ASTM 0 790 and ASTM 0 570 respectively. There are two types of material used in composite fabrications. There are raw and treated fibers. Treated fibers have the highest tensile and flexural strength overall. The highest tensile and flexural value was at 20% fiber fractions. And it decrease once it reach the highest value. Treated fiber also reduces their capability in water absorption.